2021
DOI: 10.5935/1518-0557.20210030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intracytoplasmic Morphologically Selected Sperm Injection (IMSI) on Birth Defects: A Systematic Review and Meta-Analysis

Abstract: Objective: It is generally accepted that the incidence of birth defects in spontaneously conceived children ranges between 2.0-4.0%. However, several studies have shown that babies born after assisted reproductive technology (ART) procedures tend to present more congenital malformations than naturally conceived children, with 6.5% of the children born after intracytoplasmic sperm injection (ICSI) presenting birth defects. The use of high magnification sperm selection before ICSI was introduced in the early 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Numerous discrepancies exist in the literature, notably concerning IMSI effectiveness compared to ICSI, in improving ART results (fertilization / clinical pregnancy / live births rates / miscarriage). However, a recent systematic review and meta-analysis of an average of 4,000 live births with congenital anomalies after IMSI concluded that this technique appears to be an effective tool for reducing the incidence of structural anomalies compared to ICSI [ 59 ]. On the other hand, IMSI was shown not to alter the incidence of chromosomal anomalies i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous discrepancies exist in the literature, notably concerning IMSI effectiveness compared to ICSI, in improving ART results (fertilization / clinical pregnancy / live births rates / miscarriage). However, a recent systematic review and meta-analysis of an average of 4,000 live births with congenital anomalies after IMSI concluded that this technique appears to be an effective tool for reducing the incidence of structural anomalies compared to ICSI [ 59 ]. On the other hand, IMSI was shown not to alter the incidence of chromosomal anomalies i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The method was promising but the results were conflicting ( 87 ). Recently, Dieamant et al ( 88 ), revising the literature, found that IMSI appeared to be an effective procedure in reducing the congenital malformations in newborns compared to ICSI.…”
Section: Impact Of Sperm Morphology In Assisted Fertilizationmentioning
confidence: 99%
“…Still, uncertainty remains over whether the selection process can definitively eliminate all genetic defects in sperm within a group with highly abnormal semen parameters, especially in cases of severe oligoteratozoospermia (i.e., low sperm count and motility) [6]. Although some studies have proposed intracytoplasmic morphologically selected sperm injection (IMSI) to select the best sperm to achieve optimal pregnancy outcomes, this technique is still under investigation [7]. Many genetic factors have been implicated in male infertility, and prior studies have consistently demonstrated that individuals experiencing severe oligozoospermia (i.e., low sperm count) and teratozoospermia (i.e., abnormal sperm forms) have a higher incidence of sperm aneuploidy than those with normal semen parameters [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%